Statistics elements in the context of the primary school mathematic manual Lithuanian some of the west Europe country - Kazlauskienė, Aušra (Lietuvos matematikos rinkinys, 2003)
In this research we tried to determine statistics skills in the Fourth Form. This article presents a comparative point of view of the analysis of Lithuanian and other manuals. The attention is the distribution of statistics elements.